A Study on Effects of Financial Aid on Student Persistence in Dual Enrollment and Advanced Placement Participation. (November 2020) - Lin, Ching-Hui; Borden, Victor M. H.; Chen, Jyun-Hong
Despite concerted efforts to increase participation in advanced placement (AP) and dual credit (DC) programs, their efficacy remains unexplored. Drawing upon St. John's model as the conceptual framework, this study employed a discrete-time event history analysis to examine the interplay between forms of financial aid and persistence toward degree completion for students participating in DC and AP programs and enrolling in a large, multicampus, Midwestern, U.S. University. First-time, first-year baccalaureate degree-seeking students who began studies in Fall 2012 were tracked for 4 years. The findings suggest that many factors are significantly related to college success, including student demographics such as race (especially Latino identity), first-generation status, housing status, socioeconomic status, and dependency status; high school performance, AP/DC participation, and SAT or ACT scores; and financial aid, such as Pell and federal grant aid and institutional grant programs. Results suggest that receiving Pell and federal grant aid and institutional grant-in-aid consistently and significantly attenuated the risks of student departure. In relation to prematriculation college-level credits, AP participants were more likely to receive institutional grant programs, whereas DC participants were more likely to have student loans. These findings have implications regarding the efficacy of DC/AP programs in regard to their interplay with financial aid systems in affecting persistence outcomes.